The Changes of H2O2 Level and Glutathione/Glutathione dioxide Ratio with the Administration of N-Acetylcystein, Vitamin C, and Vitamin E towards in Vitro Eclampsia Human Umbilical Vein Endothelial Cell Model - Siti Candra Windu Baktiyani (Indonesian Socety of Obstetrics and Gynecology, 2010)
Objective: To identify the optimum dosage to lower H2O2 and to increase the highest ratio of Glutathione/Glutathione dioxide in the media of eclampsia HUVEC’s model with the administration of NAC, Vitamin C, and Vitamin E. Method: We compare the concentration of H2O2 and ratio of glutathione (GSH) glutathione dioxide (GSSG) in eclampsia HUVEC’s model (as control group), and administration of three different dose of N-Acetyl Cystein (NAC), vitamin C, vitamin E and combination of them. Result: The addition of NAC, vitamin C and vitamin E to eclampsia HUVEC’s model can reduce the H2O2 level and increase GSH/GSSG ratio (p < 0.05). The optimal dose for NAC administration is 2 μM, while greater dose hamper the result. Combination of three antioxidants showed the best result compare to single antioxidant. Conclusion: The lowest level of H2O2 and the highest ratio of GSH/GSSG is achieved with the administration of the combination of NAC 2 μM, Vitamin C 100 μM and Vitamin E 100 μM. [Indones J Obstet Gynecol 2010; 34-2: 64-8] Keywords: HUVECs, eclampsia plasma, antioxidant